Attitude of health professionals on organ and tissue donation for transplants along 2009 - Hospital Santa Casa de Belo Horizonte - Pereira, Walter Antônio; Arruda, Denise Magalhães Rochido; Mendonça, Rachel Capanema Ferreira; Haddad, João Paulo Amaral (Brazilian Journal of Transplantation, 2009)
Purpose: This study aims to assess the level of the knowledge of the professionals at Santa Casa de Belo Horizonte on several aspects related to the organ and tissue donation for transplants. The study included both professionals directly working in the patient care asnd the ones from the administrative and support structure, since we believe that everyone might be a knowledge multiplier on this subject in such area of operation. Methods: It was distributed 2000 (two thousand) questionnaires containing closed questions to professionals of several segments, trying to get a mixed sampling addressing several issues concerning the organ and tissue donation as well as personal data in the form of the survey. 830 questionnaires duly completed were received, which were inserted and processed using the Statistical EpiData and EPIINFO software; they was evaluated by chi-square. Result: Through the questionnaires, we evaluated that 91% of all employees are pro-organ and tissue donation, being 91.14% females and 49.51% have donors in their family; 51.56% of them reported their opinion about the organ donation to family members. As to education: 77.65% of them who answered the questionnaire had primary education and 91.57% had high school. Conclusion: We evaluated that most of the Santa Casa de Belo Horizonte health professionals are well oriented/informed as to the subject, and they showed interest in participating of trainings and lectures. Through the research, it will be possible to work aiming targeted doubts to disseminate and encourage the organ and tissue donation among health professionals, and also among the population in general, in order to increase the amount of actual donors, the organ procurement and decreasing the waiting list for transplants.